Surgical-orthodontic treatment for class II asymmetry: outcome and influencing factors - Chen, Yun-Fang (Sci Rep, 2019)
The study aimed to evaluate the treatment outcome of bimaxillary surgery for class II asymmetry and find the influencing factors for residual asymmetry. Cone-beam computed tomographic images of 30 adults who had bimaxillary surgery were acquired, and midline and contour landmarks of soft tissue and teeth were identified to assess treatment changes and outcome of facial asymmetry. The postoperative positional asymmetry of each osteotomy segment was also measured. After surgery, the facial midline asymmetry of the mandible, chin, and lower incisors improved significantly (all p < 0.01). However, the residual chin deviation remained as high as 2.64 ± 1.80 mm, and the influencing factors were residual shift asymmetry of the mandible (p < 0.001), chin (p < 0.001), and ramus (p = 0.001). The facial contour asymmetry was not significantly improved after surgery, and the influencing factors were the initial contour asymmetry (p < 0.001), and the residual ramus roll (p < 0.001) or yaw (p < 0.01) asymmetry. The results showed that bimaxillary surgery significantly improved midline but not contour symmetry. The postoperative midline and contour asymmetry was mainly affected by the residual shift and rotational jaw asymmetry respectively.